(untitled) (Global Journal of Management and Business Research, 2016)
This study has attempted to investigate the relationship between, energy consumption, CO 2 emissions and economic growth in Ethiopia, using time series data from 1970/71 to 2010/11. The finding indicates variables of interests are integrated of the same order I (1). Cointegration test approves existence of one co-integrating equation among the variables. The causality test result shows energy consumption causes Economic Growth in Ethiopia. Based on the outcome shocks to energy consumption have a negative impact on economic growth. The contributions of energy consumption to CO 2 emissions were insignificant and economic growth is positively related to CO 2 emissions. To secure the sustenance of CO 2 emissions free economic growth in Ethiopia, cost effective, carbon free, and efficient utilization of renewable energy consumption based on the country comparative advantage that consider alternative use of resources are advisable like Hydro and Geothermal.